2021
DOI: 10.3390/rs13142785
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-1 Time Series for Crop Identification in the Framework of the Future CAP Monitoring

Abstract: In this upcoming Common Agricultural Policy (CAP) reform, the use of satellite imagery is taking an increasing role for improving the Integrated Administration and Control System (IACS). Considering the operational aspect of the CAP monitoring process, the use of Sentinel-1 SAR (Synthetic Aperture Radar) images is highly relevant, especially in regions with a frequent cloud cover, such as Belgium. Indeed, SAR imagery does not depend on sunlight and is barely affected by the presence of clouds. Moreover, the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In this context, and particularly since the availability of Sentinel-1 acquisitions, advances have been made in the analysis of radar data for crop mapping, and in its combination with optical images, to create robust classification approaches for agricultural areas [29]. Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, and particularly since the availability of Sentinel-1 acquisitions, advances have been made in the analysis of radar data for crop mapping, and in its combination with optical images, to create robust classification approaches for agricultural areas [29]. Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]).…”
Section: Introductionmentioning
confidence: 99%
“…By combining Figures 4 and 5, we found that for the features that conformed with the separability requirements, the growth stage was distributed from the 251st to 280th days, that is, mid-September to early October; this stage was the maturity period of the crops [39], which means that the difference of the spectral features reached the maximum level at the maturity stage of the crops. In addition, of the features that conformed with the separability requirements, the top five features in order of importance were RE1, NDVI, Red, SWIR2, and Aerosols, and the growth stage associated with these five features was between September 17 and September 28, i.e., within this 10-day growth stage, the differences in the spectral features of the three crops were the most significant and the easiest to extract [65]. In addition, it can be thus determined that in addition to using the conventional wavebands (visible light and near infrared (NIR)) [66], the addition of 703.9 nm (S2A)/703.8 nm (S2B) from RE1 and 2202.4 nm (S2A)/2185.7 nm (S2B) from SWIR2 had important significance for crop classification [60].…”
Section: Evaluation Of the Features Selectedmentioning
confidence: 98%
“…Aiming at reducing the uncertainty and error rates of the declaration procedures, the new rules for 2020+ CAP payments provide the increased use of modern technologies during verification phases and in particular the integration of Sentinel data for monitoring and cross-compliance assessment (Beriaux et al, 2021;Campos-Taberner et al, 2019;David et al, 2021). In this regard, the development of efficient remote sensing techniques towards monitoring and regularly updated crop type mapping arises as essential to achieve the new CAP goals.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the development of efficient remote sensing techniques towards monitoring and regularly updated crop type mapping arises as essential to achieve the new CAP goals. To this end many recent crop mapping studies have documented the employment of Sentinel data along with LPIS data for developing crop classification models in Austria, Belgium, Germany, France, Spain and the Netherlands (Beriaux et al, 2021;Blickensdörfer et al, 2022;Campos-Taberner et al, 2019;David et al, 2021;Griffiths et al, 2019;Reuß et al, 2021;Sitokonstantinou et al, 2018). In most cases LPIS data * Corresponding author were utilised after the application of some basic preparation steps in order to fit the desired nomenclature and to exclude erroneous geometries and field boundaries from the analysis.…”
Section: Introductionmentioning
confidence: 99%